Assess of Environmental and Ecological Risk of Heavy Metals Originated of Reverse Osmosis Desalination Plant Effluents to Coastal Areas in the Persian Gulf - Leila Rezaei; Vali Alipour; Amir Hesam Hassani; Mohsen Dehghani (Shiraz University of Medical Sciences, 2022)
Background: the Persian Gulf ecosystem is facing degradation, so further degradation must be prevented. The present study was conducted to assess the environmental pollution risk potential of the coastal ecosystem due to heavy metal content in desalination plant's effluent.Methods: In this cross-sectional study, the researchers selected five stations in the west of Bandar Abbas beach, located at the outlet of desalination effluent canals to the shore, and two stations in the east shore (without effluent discharge) as case and control stations, respectively. The researchers collected 51 Sediment samples and measured heavy metal concentration, using an AA spectrophotometer, and assessed the potential ecological risk. They used SPSS software and the T-test to statistically analyze data.Results: The concentration means for sediments in case and control stations samples were: 40.63±16.79, 96.64±30.60, 159.74±50.65, 109.22±17.09, 205.35±86.96 mg.kg-1 and 40.15±17.21, 79.16±28.26, 152.43±90.07, 101.82±43.55, and 193.82±112.90 mg.kg-1, respectively for (Pb, Cu, Ni, Cd, and Zn). The ecological risk and Pollution Load Index were (31.72, 35.95, 3.30, 36.96, and 45.61) and (0.62, 0.63, 0.71, 0.68, and 0.9), respectively for metals mentioned order. Individual potential risk for all stations showed a low-risk degree.Conclusion: Although the heavy metals accumulated in coastal sediments due to the discharge of desalination plant effluents, severe ecological and environmental damage has not occurred. Therefore, there is still time to prevent an environmental catastrophe on the shores receiving desalination effluents. Therefore, it is recommended to all responsible persons to take the necessary measures to monitor and control the plan and reduce the discharge of effluents to the shores.